1984
DOI: 10.1007/bf00021131
|View full text |Cite
|
Sign up to set email alerts
|

The response to temperature of leaf area in tomato genotypes. I. cell size and number in relation to the area of a leaf

Abstract: An investigation was carried out into the genotypic variation in the response to temperature of leaf area in tomatoes . Differences between genotypes in the response of the area of a leaf to contrasting temperature regimes were found, and this was due to variation in the number of epidermal cells . The epidermal cell size showed little response to temperature . The results are discussed in relation to the potential for selection for improved leaf area and the development of a rapid screening test for cold tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The relationship between leaf initiation and leaf area may be determined within the apex, for example by the partitioning of cells between the leaf primordium and the cells to be reinvested in the apical dome for subsequent leaf inititation . The importance of apical development is supported by the observation that the area of a leaf is related to the number of cells, which is probably determined at an early stage (PAUL, 1984) . Many studies have been made of apical development (WILLIAMS, 1975 ;LYNDON, 1976) but genotypic variation, such as that examined in Picea (CANNELL, 1978), has been rarely reported .…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…The relationship between leaf initiation and leaf area may be determined within the apex, for example by the partitioning of cells between the leaf primordium and the cells to be reinvested in the apical dome for subsequent leaf inititation . The importance of apical development is supported by the observation that the area of a leaf is related to the number of cells, which is probably determined at an early stage (PAUL, 1984) . Many studies have been made of apical development (WILLIAMS, 1975 ;LYNDON, 1976) but genotypic variation, such as that examined in Picea (CANNELL, 1978), has been rarely reported .…”
Section: Resultsmentioning
confidence: 62%
“…In the previous paper (PAUL, 1984) variation between these genotypes in the re- sponse to temperature of the area of an individual leaf was reported . The necessary genotypic variation is thus available for selection to proceed for these two components of the total leaf area .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kö rner and MenendezRiedl (1989) examined various types of wild plant dwarfism caused by environment stress (limited amount of sunlight or water shortage, infertile soil) and revealed that even though the organs exhibited enormous differences in size within the same species, the cell size of leaves was affected very little by these kinds of stress. Paul (1984) examined the cells of differentsized leaves of cultivated tomato plants, which exhibited differences in leaf size caused by differences in growing temperatures. He reported that smaller leaves in tomatoes cultured at lower temperatures did not have smaller cells but did have fewer cells.…”
Section: Discussionmentioning
confidence: 99%